2017
DOI: 10.1136/jech-2016-208025
|View full text |Cite
|
Sign up to set email alerts
|

Air pollution and the incidence of ischaemic and haemorrhagic stroke in the South London Stroke Register: a case–cross-over analysis

Abstract: BackgroundFew European studies investigating associations between short-term exposure to air pollution and incident stroke have considered stroke subtypes. Using information from the South London Stroke Register for 2005–2012, we investigated associations between daily concentrations of gaseous and particulate air pollutants and incident stroke subtypes in an ethnically diverse area of London, UK.MethodsModelled daily pollutant concentrations based on a combination of measurements and dispersion modelling were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 22 publications
0
28
0
2
Order By: Relevance
“…Nevertheless, we found a significant association between ischemic stroke death and PM 10 exposure, but not in hemorrhagic stroke. The studies of PM and hemorrhagic stroke were limited, and the outcomes were inconsistent ( 15 , 26 , 27 ). The mechanisms of hemorrhagic stroke and air pollution might be different from that of ischemic stroke and air pollution ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, we found a significant association between ischemic stroke death and PM 10 exposure, but not in hemorrhagic stroke. The studies of PM and hemorrhagic stroke were limited, and the outcomes were inconsistent ( 15 , 26 , 27 ). The mechanisms of hemorrhagic stroke and air pollution might be different from that of ischemic stroke and air pollution ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, few studies conducted in developing countries and distinguished the effects of PM on types of stroke ( 9 , 11 , 13 ). It is still not clear whether the effect of PM on ischemic stroke is the same with hemorrhagic stroke ( 12 , 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…. 111 The authors also reported negative (but not significant ) associations between incidence of haemorrhagic stroke and an increment in concentration of 10 µg m -3 of PM10 (-14.6%, 95% CI 0.7-26.5%) and PM2.5 (-17.0%, 95% CI, 3.3-33.3).…”
Section: Overview Of Recent Human Health Studiesmentioning
confidence: 93%
“…There was no PM 10 monitoring during all periods of pregnancy (1990–1992) and only partial coverage for periods of infancy for some of the cohort (1993-). We therefore used dispersion modelling ( Atkinson et al, 2015 ; Baiz et al, 2012 ; Charpin et al, 2009 ; Bellander et al, 2001 ; Butland et al, 2017 ; de Hoogh et al, 2014 ; Gong et al, 2017 ; Hansen et al, 2016 ; Korek et al, 2015 ; Nordling et al, 2008 ; Pirani et al, 2014 ; Van den Hooven et al, 2012 ; Schultz et al, 2016 ; Vinceti et al, 2016 ) to estimate population exposure. There are, however, only a few examples of using city/regional scale dispersion modelling for historic sub-annual exposure periods for particles ( Baiz et al, 2012 ; Nordling et al, 2008 ; Heck et al, 2013 ; Gong et al, 2017 ; Rahmalia et al, 2012 ; Sellier et al, 2014 ) due to the challenge of developing detailed inventories on sources and emissions of air pollution at different spatial scales (e.g.…”
Section: Introductionmentioning
confidence: 99%